1999
DOI: 10.1007/bf02743581
|View full text |Cite
|
Sign up to set email alerts
|

The effect of melatonin on lipid peroxidation during radiotherapy in female rats

Abstract: Melatonin, in rats, reduced the level of MDA, which is elevated by radiotherapy and increased the levels of SOD and GPX, which are involved in the antioxidant system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
49
1
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 14 publications
7
49
1
3
Order By: Relevance
“…Ionizing radiation has been reported to increase the plasma and ovarian TBARS levels in rats and melatonin administration significantly decreased these levels (30). The radioprotective effect of melatonin has been attributed to several mechanisms such as scavenging of free radicals, distribution throughout the organism, ability to induce the antioxidant enzymes, and high bioavailability (31).…”
Section: Discussionmentioning
confidence: 99%
“…Ionizing radiation has been reported to increase the plasma and ovarian TBARS levels in rats and melatonin administration significantly decreased these levels (30). The radioprotective effect of melatonin has been attributed to several mechanisms such as scavenging of free radicals, distribution throughout the organism, ability to induce the antioxidant enzymes, and high bioavailability (31).…”
Section: Discussionmentioning
confidence: 99%
“…4 Lipid peroxidation is believed to be an important cause of destruction and damage to cell membranes and has been suggested to be a contributing factor to the development of oxygen radicals-mediated tissue damage. 5 Oxidative stress occurs when there is excessive free radical production and/or low antioxidant defence, and results in chemical alterations of biomolecules causing structural and functional modifications. 6 The generation of the reactive oxygen metabolites (ROMs) plays an important role in the pathogenesis of radiation-induced tissue injury.…”
mentioning
confidence: 99%
“…Peroxynitrite formation is thought to be the reason for this elevation because peroxynitrite is recognized as an intermediate reactive species that participates in many injury processes associated with oxidative damage and causes more powerful peroxydation of unsaturated fatty acids in cellular membranes than other radicals (Radi et al, 1991;Hogg et al, 1992;Van der vliet et al, 1994). Kaya et al demonstrated that radiotherapy gives rise to significant exacerbation of TBARS levels in blood and over tissues (Kaya et al, 1999).…”
Section: Discussionmentioning
confidence: 99%